2016
DOI: 10.1109/tii.2016.2585643
|View full text |Cite
|
Sign up to set email alerts
|

Smart Insole: A Wearable Sensor Device for Unobtrusive Gait Monitoring in Daily Life

Abstract: Gait analysis is an important medical diagnostic process and has many applications in healthcare, rehabilitation, therapy, and exercise training. However, typical gait analysis has to be performed in a gait laboratory, which is inaccessible for a large population and cannot provide natural gait measures. In this paper, we present a novel sensor device, namely, Smart Insole, to tackle the challenge of efficient gait monitoring in real life. An array of electronic textile (eTextile) based pressure sensors are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(107 citation statements)
references
References 17 publications
(15 reference statements)
2
102
0
Order By: Relevance
“…Similarly, wearable sensors (including those integrated in smart phones) were reported to be useful for fall risk assessment [ 20 , 21 , 22 , 23 ]. Many low-cost instrumented insole systems have also been developed [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Among the existing low-cost insole systems, different sensor technologies were implemented, such as force sensitive resistors (FSRs) [ 25 , 33 ], fabric or textile pressure sensing arrays [ 28 ], or piezoelectric sensors [ 32 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, wearable sensors (including those integrated in smart phones) were reported to be useful for fall risk assessment [ 20 , 21 , 22 , 23 ]. Many low-cost instrumented insole systems have also been developed [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Among the existing low-cost insole systems, different sensor technologies were implemented, such as force sensitive resistors (FSRs) [ 25 , 33 ], fabric or textile pressure sensing arrays [ 28 ], or piezoelectric sensors [ 32 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Smart Insole can measure step counts, step pace, swing time, and center of pressure (COP) shifting velocity, which can further infer the walking balance status and potential fall risk in real life. [19] According to Wenyao et al, [18], there are three important subsystems as shown in Figure 3 . The first subsystem is low cost sensors for gait characterization, including 48 pressure sensors, 3-axis accelerometer, 3-axis gyroscope and 3-axis compass.…”
Section: Smart Shoe Insole Systemmentioning
confidence: 99%
“…Smart sensors are sensing devices that are equipped with digital features for data processing, storage and efficient transformation of data [10][11][12]. Smart sensors automatized the zero correction, calibration, and scaling of the measured signals by using microprocessors, in contrast to meticulous design, testing, and debugging faced by the conventional analog sensors [13][14][15][16]. The sensing platform of a smartphone is the best example of smart sensing environment; it integrates multiple sensors and…”
Section: Introductionmentioning
confidence: 99%